Latviešu tautas folkolora kā tikumiskā audzinātāja vecāko klašu skolēniem ar garīgās attīstības traucējumiem - Dambe, Ligita (Latvijas Universitāte, 2007)
Darba apjoms: 55 lpp., 27 bibliogrāfiskie avoti, 7 attēli, 2 pielikumi Atslēgas vārdi: Latviešu tautas folklora, skolēni ar viegliem garīgās attīstības traucējumiem, vērtību orientācija, tikumiskā audzināšana. Pētījuma mērķis: Noskaidrot galvenos tikumiskās audzināšanas virzienus un iespējas skolēniem ar garīgās attīstības traucējumiem. Darba saturs: Diplomdarbs izstrādāts, lai veicinātu vecāko klašu skolēnu ar viegliem garīgās attīstības traucējumiem tikumisku audzināšanu un latviskuma izpratni, kas uzlabo personības veidošanās procesu. Diplomdarbam ir 3 daļas: 1.Garīgās attīstības traucējumu raksturs. 2.Tikumiskās audzināšanas loma un uzdevums speciālajā skolā. 3.Latviskuma izpratne , vērtību orientācija un tautas kultūras izmantošanas iespējas speciālās skolas audzēkņiem. Pētījuma metodes: Teorētiskās izpētes metodes, empīriskās izpētes metodes- novērošana, intervija, anketēšana. Darba rezultāti: Izpētīta skolēnu ar viegliem garīgās attīstības traucējumiem vērtību orientācija un apkopoti folkloras avoti latviskā mantojuma ētisko vērtību nostiprināšanai. Izstrādāti ieteicamie temati audzināšanas un dzīves mācības stundām. Darba izmantojamība: Pētījumu var izmantot studenti, speciālās izglītības skolotāji.

Academic Work including: 55 Pages,27 literature references,7 pictures and 2 Notes The Main Topics including: The Latvian folklore, The Personal volubility and Ethical Framework of growth for children with mental health and disabilities. Academic Purpose: The main conclusions of the research findings indicate to find most important educational ways and opportunities for children with mental disabilities. Acadeic Research Focuss: These Academic research fundings have been done to improve educational process and understanding of Latvian cultural differences, which are focusing on development and improvement of personal identity for children with mental disabilities. Academic Research has 3 parts:1. The Disturbance Character of Mental Development2. The Main Aim and Goal of education in Latvian nature and style at Special Needs Education School. 3. The understanding of Latvian cultural differences, The Validity of Personal Identity Development and possibility to use Latvian cultural differences for children at Special Needs Education School. Academic Research Methods: Theoretical research methods, Empiric research methods observation, interview, and questionnaires. Academic Research Results: As this research was based on a relatively new fun dings, which researched the personal identity and validity development and improvement of children with mental disabilities. Researched and summarized Latvian cultural differences and analyzed Latvian traditional folklore to accept ethical framework of education. Research fun dings advising theatrical framework for teaching of Life subject. Academic Research provided for students and teachers of Special Needs Education.
Latvian folklore as the moral educator of senior pupils with mental developmental disturbances
Keywords: Pedagoģija